1994
DOI: 10.1155/s0962935194000700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nedocromil Sodium on Polymorphonuclear Leukocyte Plasma Membrane

Abstract: The effect of nedocromil sodium on the plasma membrane fluidity of polymorphonuclear leukocytes (PMNs) was investigated by measuring steady-state fluorescence anisotropy of 1-[4-trimethylammonium-phenyl]-6-phenyl- 1,3,5-hexatriene (TMA-DPH) incorporated in the membrane. Our results show that nedocromil sodium 300 μM significantly decreased membrane fluidity of PMNs. The decrease in membrane fluidity of PMNs induced by fMLP was abolished in the presence of nedocromil sodium. These data suggest that nedocromil s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Lamche et al demonstrated that steroids cause a decrease in membrane fluidity of PMN 31 . Recently, we have demonstrated that nedocromil sodium can induce changes in membrane fluidity of PMN plasma membrane 32 . These changes can induce functional changes in the PMN from asthmatic subjects.…”
Section: Discussionmentioning
confidence: 71%
“…Lamche et al demonstrated that steroids cause a decrease in membrane fluidity of PMN 31 . Recently, we have demonstrated that nedocromil sodium can induce changes in membrane fluidity of PMN plasma membrane 32 . These changes can induce functional changes in the PMN from asthmatic subjects.…”
Section: Discussionmentioning
confidence: 71%